HUBUNGAN PAJANAN BISING KONTINYU TROMOL EMAS DENGAN KELUHAN DISPEPSIA PADA MASYARAKAT DESA TATELU - ., Bernie; Supit, Siantan; Engka, Joice N. A. (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: Gold is a mining commodity that has a high value. Tatelu’s gold processing is traditionally done with tromol machines that produce high intensity continous noise. Noise is a trigger of stress, which is one of the causes of dyspepsia. This study aimed to find out the relationship between continous noise exposure of the mining tromol and dyspepsia complaints among Tatelu villagers. The study was done by using a cross sectional design. The samples were divided into two groups: the control and the exposed groups. Each group consisted of 20 people. Interviews used structured questionnaires, and dyspepsia diagnostics were based on Rome Consensus III. The characteristics of samples and the prevalence of dyspepsia complaints were assessed using univariate analysis. Chi square was used to assess the relationship between continous noise exposure of the tromols with complaints of dyspepsia. The results showed that in residential areas exposed to noise, 70% of the samples had complaints of dyspepsia, while in the control area there were only 25%. The results of the statistical analysis using the Chi square showed the value x2count (8.12) > x2table (3.84) and the P-value = 0.004 < 0.05 with α < 5%. Conclusion: There was a significant relationship between the continous noise exposure from the gold tromols with the complaints of dyspepsia among Tatelu villagers. Keywords: noise, stress, dyspepsia. Abstrak: Emas merupakan komoditi tambang yang mempunyai nilai tinggi. Pengolahan emas di desa Tatelu dilakukan secara tradisional dengan menggunakan mesin tromol yang menghasilkan bising kontinyu dengan intensitas tinggi. Bising merupakan pemicu terjadinya stres yang merupakan salah satu penyebab terjadinya dispepsia. Penelitian ini bertujuan untuk mengetahui hubungan pajanan bising kontinyu tromol emas terhadap keluhan dispepsia pada masyarakat desa Tatelu. Penelitian ini menggunakan rancangan cross sectional. Sampel terdiri dari 20 orang kelompok kontrol dan 20 orang kelompok terpajan. Penelitian menggunakan teknik wawancara dengan kuesioner terstruktur. Diagnosis dispepsia ditegakkan dengan kriteria Konsensus Roma III. Karakteristik sampel dan prevalensi keluhan dispepsia dinilai dengan analisis univariat. Hubungan antara pajanan bising kontinyu tromol emas dengan keluhan dispepsia dinilai dengan chi square. Hasil penelitian menunjukan pada daerah terpajan bising 70% sampel mengalami dispepsia sedangkan pada daerah kontrol hanya 25%. Hasil analisis statistika dengan menggunakan chi square menunjukan nilai x2hitung (8,12) > x2tabel (3,84) dan nilai P = 0,004 < 0,05 dengan < 5 %. Simpulan: Terdapat hubungan bermakna antara pajanan bising kontinyu tromol emas dengan keluhan dispepsia pada masyarakat Desa Tatelu. Kata kunci: bising, stres, dispepsia.